Human Now versus Human Over Time. When Instrumental Rationality and Utility are not Enough - Ostapiuk, Aleksander (Panoeconomicus, 2018)
The goal of this article is to show that instrumental rationality and utility that have been used in economics for many years does not work well. What is presented in the article is how significant the influence of utilitarianism has been on economics and why the economists get rid of humans’ goals and motivations. It is shown in the article that the human who decides in present is absolutely different from the human who decides over time. Many economists neglected this problem because they wanted to have an effective and simple model. Becker’s economic method is presented as a dead end to which economics has been brought to. It is impossible to connect different selves of one human being by using the utility measure. The works of Schelling and J.S. Mill are used to explain this impossibility. The conclusion of this article is that instrumental rationality and utility have affected economics significantly. But, this simplified view on human nature is no longer valid. Hence, economics needs to think not only about the means but also about the human goals. Economics needs to rebuff relativism and show people how to achieve well-being. If we want to help people with their self-governance, we will have to choose reason over emotions. Key words: Instrumental rationality, Utilitarianism, Choice over time, Multiple selves, Wellbeing. JEL: B00, B4, B5, D91. Čovek sada i čovek kroz vreme. Kad instrumentalna racionalnost i korisnost nisu dovoljni Cilj rada je da pokaže da instrumentalna racionalnost i korisnost koji se u ekonomiji koriste već duži niz godina ne funkcionišu dobro. Ono što je predstavljeno u radu je nivo uticaja utilitarizma na ekonomiju i zašto se ekonomisti oslobađaju ljudskih ciljeva i motivacije. U radu je pokazano da se čovek koji donosi odluku za sada apsolutno razlikuje od čoveka koji donosi odluku kroz vreme. Mnogi ekonomisti su zanemarili ovaj problem jer su želeli da imaju efikasan i jednostavan model. Bekerova ekonomska metoda predstavljena je kao slepa ulica do kojeg je ekonomija dovedena. Nemoguće je povezati različite osobine jednog čoveka korišćenjem mere korisnosti. Radovi Šelinga i Mila se koriste za objašnjenje ove nemogućnosti. Zaključak rada je da su instrumentalna racionalnost i korisnost značajno uticali na ekonomiju. Ali, ovo pojednostavljeno gledište na ljudsku prirodu više nije validno. Dakle, ekonomija mora razmišljati ne samo o sredstvima već i o ljudskim ciljevima. Ekonomija treba da umanji relativizam i pokaže ljudima kako da postignu blagostanje. Ako želimo da pomognemo ljudima u njihovoj samoupravi, moraćemo da izaberemo razum naspram emocija. Ključne reči: Instrumentalna racionalnost, utilitarizam, izbor s vremenom, višestruke osobine, blagostanje.